The Influence of Transformational Leadership Style, Work Discipline, and Work Environment on Employee Performance of The Regional Disaster Management Agency of Central Maluku Regency - Eva Rianita Latuconsina; N. C. Lewaherilla; A. Risambessy (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2023)
The Regional Disaster Management Agency (BPBD) as an agency that has always been at the forefront of the field of disaster in the Central Maluku Regency region cannot be separated from its success from the human resources in it, and employees who are an important element in achieving the vision and mission and goals of the organization based on the level of achievement of its performance. . For this reason, employees are always required to produce good performance because good or bad performance will affect the goals of the organization. In this case an organization needs a leader, with the presence of a leader can move or direct the organization in achieving its goals. In addition to leadership factors, work discipline and an adequate work environment are also needed and support the implementation of work so that the performance of employees who are expected to increase can be carried out properly. The research was conducted at the Regional Disaster Management Agency (BPBD) of Central Maluku Regency. The type of data used is qualitative data. Data was collected through a questionnaire to 31 respondents. Data analysis technique using multiple linear regression analysis. Data processing using SPSS. The results of the study show that: (1) transformational leadership style directly has a positive and significant effect on employee performance, (2) work discipline has a positive and significant effect on employee performance, (3) work environment has a positive and significant influence on employee performance.